How do Eurozone stock markets react to ECB unconventional monetary policy announcements? A comparison accross countries - Alves, João Francisco Ventura Santos (2020)
This research applies a short-term event study methodology to estimate the abnormal returns of the Eurozone indices around the European Central Bank’ unconventional monetary announcements. It considers all the publicly available nonstandard policy statements between September 2008 and the end of 2016. The ones related to Asset Purchase Programs had a significant positive effect on the Italian, Portuguese and Spanish stock markets throughout the entire sample while the German and Dutch indices show a negative one. Moreover, it is observable that some indices such as the BEL20 delivered significant negative cumulative abnormal returns when the European Central Bank announced the first tools concerning the Provision of Liquidity during the crisis, but nowadays the reaction to this kind of events is almost null.